PELATIHAN MEDIA APLIKASI QUIZWHIZZER DALAM UJI KOMPETENSI KEMAMPUAN INTELEKTUAL MAHASISWA - Nasution, Atikah Rahmah; Subagiharti, Heni (Smart Education, 2025)
Abstract: This community service activity is expected so that the community, especially students, understand the importance of understanding the use of application media. Increasing students' awareness of the importance of being literate in the world of technology, especially in this 5.0 era or its transition, humans must understand and use sophisticated technology, especially applications that support increasing their understanding of knowledge or intellectual abilities. The purpose of this community service is to provide experience and improve students' competency skills, both with the help of the quizwhizzer application media. Keyword: Quizwhizzer, Intellectual Ability Competency test, College Student Abstrak: Kegiatan pengabdian kepada masyarakat ini diharapkan agar masyarakat khususnya mahasiswa paham akan pentingnya dalam memahami penggunaan media aplikasi. Peningkatan kesadaran para mahasiswa akan pentingnya melek akan dunia teknologi terutama pada zaman 5.0 ini atau transisinya manusia harus memahami dan menggunakan teknologi canggih terutama aplikasi yang menunjang peningkatan pemahaman kemampuan pengetahun atau intelektual mereka. Tujuan dari pengabdian kepada masyarakat ini adalah memberikan pengalaman dan meningkatkan keterampilan kompetensi kemampuan mahasiswa baik dengan dibantukannya media aplikasi quizwhizzer. Kata kunci: Quizwhizzer, Uji Kompetensi Kemampuan Intelektual, Mahasiswa.